Pentingnya Peningkatan Keterampilan Teknologi Informasi dan Komunikasi bagi Mahasiswa Universitas Teuku Umar untuk Persiapan dalam Dunia Kerja - Indah Levina (Indonesian Journal of Teaching and Teacher Education, 2021)
This research was conducted with the aim of knowing the preparation of students at Teuku Umar University in West Aceh Regency in improving their skills to prepare themselves to enter the world of work in the future which is all digital. This research was conducted with a qualitative research with a case study approach. Techniques in data collection are carried out through observation, interviews, and literature studies as a support in conducting research. This study draws the conclusion that there are still students who have not received something more specific and specific in the ICT field in detail or in depth in teaching the courses applied in one semester. So that it makes students a little difficult to apply computers or ICT widely when heading in preparation for the world of work in the future.